Bird evaluation at El Paraíso lagoon, Lima, Peru - Cruz, Zoila (2007)
This study was carried out at El Paraíso lagoon, Lima, Peru, from April 1999 to April 2000. The main goals was determinated the birds specifi c diversity, the population density of main cinegetic bird families and the determination of the most important microhabitats for the studied groups. 81 birds species (19 species are new for the area) were reported, distribuited in 62 generas and 35 families. 46% of the diversity is given for the following families: Scolopacidae (14%), Ardeidae (10%), Laridae (7%), Anatidae (5%), Charadriidae (5%) and Columbidae (5%). The Rallidae family is the most abundant and is represented for two species Gallinula chloropus“Common Moorhen” y Fulica ardesiaca“Slate-colored Coot”. It is given recommendations for the conservation of the area.